2000
DOI: 10.1073/pnas.97.13.7051
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetic and genomic attributes in the success of polyploids

Abstract: P olyploidy, the presence of more than two genomes per cell, is a significant mode of species formation in plants and was one of the topics closest to the heart of Ledyard Stebbins. In Variation and Evolution in Plants, Stebbins (1) devoted two chapters to polyploidy and addressed the following issues: the frequency, taxonomic distribution, and geographic distribution of polyploidy; the origins of polyploidy and factors promoting polyploidy; the direct effects of polyploidy; the polyploid complex; the success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
692
5
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 931 publications
(716 citation statements)
references
References 97 publications
11
692
5
8
Order By: Relevance
“…New methods for synthetic polyploidization of plants through the use of spindle inhibitors, such as colchicine or dinitroanilines (for example, oryzalin and trifluralin), have been developed and successfully used in several plants (Vaughn and Lehnen, 1991;Hancock, 1997;Zlesak et al, 2005;Dhooghe et al, 2009). However, synthetic polyploidization has contributed little to crop improvement, likely owing to fixed heterozygosity (Soltis and Soltis, 2000). Contrary to the assumption of Stebbins (1950), Harlan and De Wet (1975) showed that almost all plant species produce 2n gametes with some frequency.…”
Section: Introductionmentioning
confidence: 99%
“…New methods for synthetic polyploidization of plants through the use of spindle inhibitors, such as colchicine or dinitroanilines (for example, oryzalin and trifluralin), have been developed and successfully used in several plants (Vaughn and Lehnen, 1991;Hancock, 1997;Zlesak et al, 2005;Dhooghe et al, 2009). However, synthetic polyploidization has contributed little to crop improvement, likely owing to fixed heterozygosity (Soltis and Soltis, 2000). Contrary to the assumption of Stebbins (1950), Harlan and De Wet (1975) showed that almost all plant species produce 2n gametes with some frequency.…”
Section: Introductionmentioning
confidence: 99%
“…How is dosage balance achieved when the genome suddenly contains additional copies of a gene? Such questions have been explored in plants (Soltis and Soltis, 2000;Wendel, 2000;Chen et al, 2004;Comai, 2005). What are the mechanisms leading to retention or loss of a duplicated gene?…”
mentioning
confidence: 99%
“…These observations led to the prediction that polyploidization will rarely be observed in animals but more frequently in plants. However, with the discovery of many additional polyploid species [35], the emergence of molecular methods in the 1980s and 1990s and the increasing availability of genomic sequence, much of the accepted pre-genomic lore concerning polyploids has been questioned [36][37][38]. This has led to a resurgence of studies of the mechanisms of polyploidization, the physiological conditions that enable polyploids to arise, positive and negative forces acting on neopolyploids and the extent to which polyploidization represents special evolutionary opportunities.…”
Section: Introductionmentioning
confidence: 99%